Pengenalan Aplikasi dan Website RedDoorz kepada Generasi Milenial di Kawasan Surabaya - Dini Aulia Cahyani; Ika Korika Swasti (ManBiz: Journal of Management and Business, 2026)
The rapid development of digital technology has significantly changed people’s behavior patterns, particularly in fulfilling travel and accommodation needs. Millennials, as a productive age group closely associated with digital technology, tend to utilize applications and websites to access information and conduct online transactions. However, some millennials still lack optimal understanding regarding the use of digital accommodation booking platforms, including the RedDoorz application and website. This community service activity aims to introduce and socialize the use of the RedDoorz application and website to millennials through flyer distribution activities conducted in Surabaya and its surrounding areas. The methods used include direct socialization, distribution of informational flyers, and brief explanations regarding the features, benefits, and ease of use of the RedDoorz platform. The results indicate an increased level of understanding and interest among millennials in using the RedDoorz application and website as a practical, efficient, and affordable accommodation booking solution. This activity is expected to contribute to improving digital literacy while supporting the development of technology-based tourism and hospitality sectors.